Influence of the menstrual cycle and its phases on the performance of olympic weightlifting athletes - Caporale, A. (EWF Scientific Magazine, 2017)
The data relating to the performance of female lifters showed a high percentage of null lifts in the pre-menstrual and menstrual phase, regardless of the various quantitative differences relating to the individual athletes. However, several aspects are still to be analysed, as we also detected the presence of important variables which may influence the performance ability of female athletes, such as: o the influence of changes in body temperature on performance, secondary to the menstrual cycle; o changes in respiratory rate and pulmonary ventilation in the different phases of the cycle, affecting performance and response during training; o the trend of hematological parameters and iron metabolism, also in function of the type of nutrition; o the ability of expression and the power of the vegetative nervous system as a modulator of the responses to workloads and recovery index; o the central regulation of effort and its psychological aspects, which we know to be very different between men and women, at least in practical expression. All the above was confirmed in the answers to a questionnaire compiled by the athletes in question, but also by the trend of the training sessions appropriately assessed month by month, so as to discover any possible discrepancies between "cycle" period, the "pre-menstrual" period (circa 5 days before menstruation) and the "absence of cycle" period. Observing the "Total" graphs - the graphs which define the sum values obtained by the four athletes, in all three exercises (Snatch - Clean & Jerk - Front Squat) - the percentage of null lifts is just below 50% of the total lifts during the trial period. Whereas, evaluating the values obtained by observing only the lifts carried out with load percentages in the range of 80% - 95%, there is a net percentage of 50% of null lifts in relation to the total lifts of the entire period. Considering that the margin of "error" in maximum performance is statistically verified, regardless of gender and of the hormonal state of an athlete, we wanted to specifically isolate this type of test, as - by analysing only the period of a "cycle" - it shows, in fact, that the inherent difficulty in achieving maximum performance in this period is completely confirmed by 100% null lifts in the Snatch, since this exercise requires a high level of coordination and consequently, for its execution requires an optimal mental and physical state; whereas, in the Clean & Jerk and the Front Squat, the percentage of null lifts is not too far from the percentages obtained with loads between 80% and 95%, as these two exercises require less coordination than the Snatch, and in a progressive manner. Moving on from the examination of the entire group to that of an individual athlete, the general considerations remain the same, but naturally, a subjective evaluation shows, specifically, how the variations determined by the presence of the "cycle" can affect each athlete.